If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 7y = 8 Solving ax + 7y = 8 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7y' to each side of the equation. ax + 7y + -7y = 8 + -7y Combine like terms: 7y + -7y = 0 ax + 0 = 8 + -7y ax = 8 + -7y Divide each side by 'x'. a = 8x-1 + -7x-1y Simplifying a = 8x-1 + -7x-1y
| 3(x+0.1)-4(x-0.5)=5.4 | | -2y-5=y+4 | | 3d-11-7d=5 | | 3(x+0.1)-4(x-0.5)=54 | | 5(m-2)=8(m-2) | | log[2](3x+6)=4 | | 5x(x+5)=0 | | y=(x^2-5)(x^2-x^3) | | x=7i | | 152=-3+5(1+6n) | | -148=3(4+4x)+8x | | (4x+2)-(3x-3)=8 | | -11=x-18 | | (17/30)/(3)=z | | (17/30)/(1/3)=z | | 0=-16t^2+128-256 | | 0=-16t^2+128t-192 | | 12-3x=5x-12 | | (9/10)-(1/3)=x | | 5.972*2.71828=389.40563584 | | 7x-8(x+1)-3=3(x+4)-4(x+1) | | 3x+7=9x+3 | | 3n-5=-21 | | 33.33333=4+-1 | | c=0.75y+50 | | x+26=2x+4 | | 2x+y=110 | | (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 |